2009
DOI: 10.1098/rspb.2009.0704
|View full text |Cite
|
Sign up to set email alerts
|

The origin of ascophoran bryozoans was historically contingent but likely

Abstract: The degree to which evolutionary outcomes are historically contingent remains unresolved, with studies at different levels of the biological hierarchy reaching different conclusions. Here we examine historical contingency in the origin of two evolutionary novelties in bryozoans, a phylum of colonial animals whose fossil record is as complete as that of any major group. In cheilostomes, the dominant living bryozoans, key innovations were the costal shield and ascus, which first appeared in the Cretaceous 85 -95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 29 publications
(42 reference statements)
2
36
0
Order By: Relevance
“…2E herein), from marginal pore chambers. Circum-opesial spines present; orificial spines with a flexible joint at base; opesial spines with or without a flexible joint (Dick et al, 2009). Reproductive zooids have a reduced, vestigial kenozooidal ooecium (e.g., Figs.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…2E herein), from marginal pore chambers. Circum-opesial spines present; orificial spines with a flexible joint at base; opesial spines with or without a flexible joint (Dick et al, 2009). Reproductive zooids have a reduced, vestigial kenozooidal ooecium (e.g., Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Dick et al (2009) identified this species as C. disjunctus due to the large, paired avicularia and somewhat disjunct zooids with small lacunae evident between them in SEM images; at that time, C. disjunctus was the only known species with similar characters. Cauloramphus cheliferoides and C. disjunctus are very similar in opesia and zooid size, but differ in many other characters (Table 2), including avicularium length/depth ratio; avicularium position; and number of orificial, opesial, and total spines.…”
Section: Cauloramphus Disjunctusmentioning
confidence: 99%
See 3 more Smart Citations